Future school well-being : a qualitative study on the imagined futures of Finnish youth - Nikula, Elina; Järvinen, Tero; Laiho, Anne (Routledge, 2025)
Supporting the well-being of young people is one of a school’s key goals. We examined school well-being from the perspective of young people by asking them what kinds of images they had of school well-being in future schools. Using a qualitative research design to obtain an open and interpretive response, we analysed essays written by Finnish general upper secondary school students (n = 89). With an analysis that utilised Dator’s (2009. ‘Alternative futures at the Manoa School.’ Journal of Futures Studies 14 (2): 1–18) archetypes of future images, Allardt’s (1996. ‘Hyvinvointitutkimus ja elämänpolitiikka’ [Welfare research and life policy]. Janus 4 (3): 224–241) sociological model of well-being, and components of Konu and Rimpelä’s (2002. ‘Well-being in schools: a conceptual model).’ Health Promotion International 17 (1): 79–87. doi:10.1093/heapro/17.1.79) school well-being model, we present a versatile perspective on school well-being via four alternative future images. The students conveyed desirable and threatening factors at both societal and individual levels, revealing tensions in the young people’s views and experiences regarding their acceptance or their criticism of the current neoliberal educational policies, with their emphasis on individual responsibility, efficiency, and competition. This study contributes to the literature on young people’s school well-being by using a future-oriented approach that involved describing alternative futures. This enables us to explore our understanding of social change and to examine possibilities for future directions in schooling.